Implementation of the Medicare Part D Prescription Drug Benefit is Associated with Antiretroviral Therapy Interruptions - Das-Douglas, Moupali (2008)
Antiretroviral (ARV) treatment interruptions are associated with virologic rebound, drug resistance, and increased morbidity and mortality. The Medicare Part D prescription drug benefit, implemented on January 1st, 2006, increased consumer cost-sharing. Consumer cost-sharing is associated with decreased access to medications and adverse clinical outcomes. We assessed the association of Part D implementation with treatment interruptions by studying 125 HIV-infected homeless and marginally housed individuals with drug coverage receiving ARV therapy. Thirty-five percent of respondents reported Medicare coverage and 11% reported ARV interruptions. The odds of ARV interruptions were six times higher among those with Part D coverage and remained significant after adjustment. The majority of Part D-covered respondents reporting ARV interruptions cited increased cost as their primary barrier. Directed interventions to monitor the long-term effects of increased cost burden on interruptions and clinical outcomes and to reduce cost burden are necessary to avoid preventable increases in morbidity and mortality.